Therapeutic Communication of Health Workers with Patients in Complementary and Alternative Medicine - Astri Dwi Andriani (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung Sunan Gunung Djati Bandung, 2022)
Complementary and Alternative Medicine is an alternative for patients who want to take treatment outside of standard medical treatment, especially for groups of patients suffering from Priority Non-Communicable Diseases (NCDs). This phenomenon is then studied using the constructivist paradigm, qualitative methods, case study approaches, and social construction theory. Data collection techniques were participant observation for a year, interviews with six key informants and 19 resource triangulation, literature study, and document study. The data analysis technique uses the Miles and Huberman Interactive model, and the validity test uses data triangulation. The aims of this study were:1) to explore descriptive knowledge about holistic health;2)to find out the reasons for using self-healing as a priority treatment for NCDs patients; and 3)to create a therapeutic communication model for self-healing therapy. The results showed:1)holistic health is a state of well-being and balance between physical, mental, emotional, social, spiritual, and environmental conditions;2)self-healing is an alternative for Priority NCDs patients who want to reduce the adverse effects of drug side effects; and 3)communication delivered using therapeutic principles will affect the patient's perception of understanding the message so that it affects patient trust and patient compliance, accelerates the patient's adaptation process, and improves the patient's health condition holistically. This research is also expected to provide an overview of self-healing methods and become an alternative reference in the world of health as a solution for prioritising non-communicable diseases.